Linguistik Arab dan Ruang Lingkup Linguistik Modern : pengertian linguistik, manfaat linguistik, ruang lingkup linguistik modern - Hikmatul KhusniahKhusniah; Nandang Sarip Hidayat; Muhammad Muhakkim (Program Studi Pendidikan Bahasa Arab Sekolah Tinggi Bahasa Arab dan Dakwah Masjid Agung Sunan Ampel Surabaya, 2024)
Language is a sound that is spoken to communicate and convey something. Language is also used to exchange ideas, learn and improve the ability to interact between fellow humans. One of the things that must be learned in language is linguistics. Linguistics is studying language scientifically. The main aim of linguistics is to examine/study a language descriptively. Therefore, this research aims to find out what is meant by linguistics and what the scope of modern linguistics studies are. This research is a library research method research. The data analysis technique used is content analysis and the data is presented in a qualitative descriptive manner, this is because this article uses the library research method. Meanwhile, the conclusion of this research is that there are 5 scopes of modern linguistic studies, namely phonetics, phonology, morphology, syntax and semantics.